PENGARUH KETERAMPILAN MIND MAPPING TERHADAP KETERAMPILAN METAKOGNITIF SISWA KELAS V - Prasetiya, Akhid (Universitas Negeri Surabaya, 2019)
ABSTRACTThis research aims to identify and explain (the effect on the mind mapping skills against 5th grade students metacognitive skills in the Mathematics subjects of materials two-dimentional figure. The research design used was Quasi Experimental Designs. The subjects were 5th grade students of SD Negeri Sungapan 1 second semester of 2015/2016 academic year. Data were obtained through two instruments (1) metacognitive questionnaire sheet and (2) the mind mapping skills observation sheets. While the mind mapping observation skills is done by an observer in the experimental classroom. To ensure the accuracy and confidence in the results of research, the instrument has gone through stages of validity and reliability. The results showed that the average score of the initial questionnaire metacognitive skills in the experimental class amounted to 68.12 (51.77 points). Meanwhile, the average score of the final questionnaire metacognitive skills in the experimental class amounted to 86.54 (65.77 points). Based on the regression test on the measurement data of student?s mind mapping skills questionnaire data metacognitive experimental class can be seen the value of R square of 0.166, or 16.6% , This means that the influence of mind mapping variable to variable metacognitive skills by 16.6%. With a significance value of 0.025 which is under 0.05 proved there is influence of the mind mapping skills against metacognitive skills. According to those experiment result conclude that: there is significant influence mind mapping skills against 5th elementary students metacognitive skills in the Mathematics subject materials two-dimentional figure. Keywords: metacognitive skills, mind mapping skills. ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui dan menjelaskan pengaruh keterampilan mind mapping terhadap keterampilan metakognitif siswa kelas V SD pada mata pelajaran Matematika materi geometri bangun datar. Desain penelitian yang digunakan adalah Quasi Experimental Designs. Subjek penelitian adalah siswa kelas V SD Negeri Sungapan 1 semester genap tahun pelajaran 2015/2016. Data penelitian diperoleh melalui dua instrumen (1) lembar angket metakognitif dan (2) lembar observasi keterampilan mind mapping. Angket metakognitif diberikan kepada subjek penelitian sebelum dan sesudah perlakuan (penerapan metode mind mapping). Sementara observasi keterampilan mind mapping dilakukan oleh seorang observer pada kelas eksperimen. Untuk menjamin keakuratan dan kepercayaan hasil penelitian, maka instrumen telah melalui tahap uji validitas dan reabilitas. Hasil penelitian menunjukkan bahwa rata-rata nilai angket awal keterampilan metakognitif pada kelas eksperimen sebesar 68,12 (51,77 poin). Sedangkan, rata-rata nilai angket akhir keterampilan metakognitif pada kelas eksperimen sebesar 86,54 (65,77 poin). Dengan demikian terdapat peningkatan sebesar 18,42 (14 poin). Berdasarkan hasil uji regresi pada data pengukuran keterampilan mind mapping siswa terhadap data angket metakognitif kelas ekperimen dapat diketahui nilai R square sebesar 0,166 atau 16,6%. Artinya besarnya pengaruh variabel mind mapping terhadap variabel keterampilan metakognitif sebesar 16,6%. Dengan nilai signifikansi sebesar 0,025 yang berada di bawah 0,05 terbukti ada pengaruh ketrampilan mind mapping terhadap ketrampilan metakognitif. Melalui eksperimen penerapan metode mind mapping terhadap keterampilan metakognitif siswa maka diperoleh hasil yaitu: terdapat hubungan yang signifikan keterampilan mind mapping terhadap keterampilan metakognitif siswa kelas V SD pada mata pelajaran Matematika materi bangun datar. Kata Kunci: keterampilan metakognitif, keterampilan mind mapping.